Prediction of Compressive Strength of Concrete incorporating fine recycled aggregate using regression analysis - Ismail, YArshd; Al-Luhybi,Ashtar S; Mohamma,dKhalaf (University of Eloued جامعة الوادي, 2024)
The practical use of recycled aggregate produced from crushing concrete waste in the production of new concrete reduces the consumption of natural aggregate and also reduces the amount of concrete waste that ends up in landfills. This study addresses the properties of concrete containing recycled fine aggregate (RFA) obtained from existing waste in Mosul. Four sets of concrete mixtures with different compressive strength (25, 30, 35 and 40MPa) were prepared, and for each strength, the effect of changing the replacement ratios of natural fine aggregate with recycled fine aggregate was studied, where four different ratios (0, 10, 20, 30) % of recycled fine aggregate (RFA) were adopted. The focus was on the compressive strength of concrete containing recycled fine aggregate due to the importance of this property as an indicator of concrete feature and the main determinant of its quality and the most important factor in design. The results showed a gradual decrease in the fresh properties of concrete containing recycled fine aggregate, such as slump and fresh density, as the proportion of recycled aggregate increased. However, there was an improvement in the compressive strength of the concrete mixes. Based on the practical results, equations were derived to predict the compressive strength of concrete containing recycled fine aggregate. According to the theoretical results obtained through analysis of variance (ANOVA), it was found that adding recycled fine aggregate at a rate of 20% is considered the best proportion, although the change in compressive strength is not significant
Article
Keywords: Recycled fine aggregate; Compressive strength; Slump; Analysis of variance